The Rise and Decline of ArabuTamil Language for Tamil Muslims - Zubair, KMA Ahamed (IIUC Studies, 2016)
The Arab Muslim Traders and the native Tamil converts to Islam in Tamilnadu state of India and Sri Lanka came into closer contact as a result of their commercial activities. They were bound by a common religion, but separated by two different languages They felt the necessity for a link-language. They started to write Tamil in an adapted Arabic script called Arabu-Tamil. The Arabu-Tamil or Arwi script represents the Tamil language using an Arabic style of scripts. From eighth century to nineteenth century, this language enjoyed its popularity among Tamil speaking Muslims of Tamil Nadu and Sri Lanka. The valuable and useful ideas of Tamil Muslim minds were conveyed in Arabicized Tamil called Arabu-Tamil. It rendered a most useful service for the advancement and progress of Arab and Tamil cultures. However, the beginning of the twentieth century saw the decline of Arwi language. And no step was taken to arrest this decline. The study analyses its rise and decline as a language of Tamil Muslims. IIUC Studies Vol.10 & 11 December 2014: 263-282